PERAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING HUBUNGAN CUSTOMER EXPERIENCE, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG PRODUK UNIQLO - Hisyam, Finishia Malihah; Aqmala, Diana; Zakaria, Fakhmi; Oktoriza, Linda Ayu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This research analyzes the impact of customer experience, product quality, and price perception on repurchase intention for Uniqlo products.Method: This research used a quantitative approach, collecting data through questionnaires and interviews using a purposive sampling technique with 126 respondents who wear Uniqlo. Data analysis was conducted using SmartPLS 4 through outer model, inner model, and mediation testing.Results: The findings indicate that customer experience, product quality, and price perception have a positive and significant influence on repurchase intention, with brand image acting as an indirect mediating variable. These findings provide practical implications for developing marketing strategies to increase repurchase intention.Conclusions and Recommendations: Customer experience, product quality, and price perception have a significant positive influence on repurchase intention for Uniqlo products, both directly and indirectly through brand image. Further research is recommended to use different objects, add additional independent variables, and apply longitudinal data. For companies, it is important to maintain and strengthen a brand image that is aligned with product quality and service in order to maintain loyalty and encourage repeat purchases. Keywords: Brand Image, Customer Experience, Product Quality, Price Perception, Repurchase Intention